Characteristics of sleep disturbance across two waves of the COVID-19 pandemic among nursing staffs - Pei-Jhen Wu; Wen Chun Wang; Chin-Lien Liu; Guei-Ging Lin; Ying-Ying Lo; Frank Huang-Chih Chou (Sleep Medicine: X)
Objectives: COVID-19 has impacted human lifestyles, including sleep quality. For nursing staff, sleep disorders not only impact their health and daily lives but also have implications for patient safety. The objective of this study is to explore the impact of the COVID-19 pandemic on the psychological and social aspects of nursing staff and the factors influencing their sleep quality through a two-wave survey. Methods: Nursing staff from a psychiatric hospital in southern Taiwan were recruited in two waves during the COVID-19 epidemic. The level of sleep disturbance and related variables, such as Lo's Healthy and Happy Lifestyle Scale (LHHLS) and Societal Influences Survey Questionnaire (SISQ), were collected through self-report questionnaires. Factors related to the level of sleep disturbance were examined using univariate linear regression and multilevel linear regression. Results: 508 nursing staff members were included in the study, with 254 members in each wave. A significant difference was found between the two waves in the positive thinking of LHHLS and all subscales of SISQ. During the second wave, sleep disturbances were mainly related to self-efficacy, positive thinking, social anxiety, and social desirability. At the fourth wave, sleep disturbances were mainly related to self-efficacy, positive thinking, and social anxiety. However, these effects change when the trend of the epidemic shifts, and other factors are taken into account. Conclusions: This study analyzed the factors related to the sleep quality of nursing staff during the COVID-19 pandemic. We preliminarily explored the impact of the COVID-19 pandemic on the sleep quality of nursing staff. However, determining whether the end of the epidemic has reduced the impact on nursing staff requires further research.